Inflammation produced by senescent osteocytes mediates age-related bone loss - Wang, Zixuan; Zhang, Xiaofei; Cheng, Xing; Ren, Tianxing; Xu, Weihua; Li, Jin; Wang, Hui; Zhang, Jinxiang (Frontiers in Immunology, 2023)
Purpose: The molecular mechanisms of age-related bone loss are unclear and without valid drugs yet. The purpose of this study was to explore the molecular changes that occur in bone tissue during age-related bone loss, to further clarify the changes in function, and to predict potential therapeutic drugs. Methods: We collected bone tissues from children, middle-aged and elderly people for protein sequencing, compared the three groups of proteins pairwise, and the differential expressed proteins (DEPs) in each group were analyzed by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG). K-mean cluster analysis was then used to screen out proteins that continuously increased/decreased with age. Canonical signaling pathways that were activated or inhibited in bone tissue along with increasing age were identified by Ingenuity Pathway Analysis (IPA). Prediction of potential drugs was performed using the Connectivity map (CMap). Finally, DEPs from sequencing were verified by western blot and drug treatment effect was verified by quantitative real-time PCR. Results: The GO and KEGG analysis shows that the DEPs are associated with inflammation and bone formation with aging, and IPA analysis shows pathways such as IL-8 signaling and acute phase response signaling were activated, while glycolysis Ⅰ and EIF2 signaling were inhibited. A total of 9 potential drugs were predicted, with rapamycin ranking the highest. In cellular experiments, rapamycin reduced the senescence phenotype produced by H2O2 stimulated osteocyte-like cell MLO-Y4. Conclusions: With age, inflammatory pathways are activated in bone tissue and signals that promote bone formation are inhibited. This study contributes to the understanding of the molecular changes that occur in bone tissue during age-related bone loss and provides rapamycin as a drug of potential clinical value for this disease. The therapeutic effects of the drug are to be further studied in animals.